(untitled) (Health and Biosciences, 2022)
ABSTRACT Rheumatoid arthritis is a chronic inflammatory autoimmune disease, which affects mostly the joints and can destroy these tissues when left untreated, reducing body movements, and reducing an individual’s quality of life. The standard treatment is based on the use of disease-modifying antirheumatic drugs (DMARDs), non-steroidal anti-inflammatory drugs and corticosteroids. However, with the advent of biotechnology appeared the biologic drugs, which offered a new treatment option for rheumatoid arthritis. This present work aims to conduct an integrative review by literature survey in scientific databases to answer the question “what are the advantages and disadvantages of using biological drugs compared to conventional treatment in cases of rheumatoid arthritis?”. Articles were selected based on date published and their relevance to the topic, using the terms biopharmaceuticals, biological medicines and rheumatoid arthritis as keywords, in English and Portuguese. Articles whose title, abstract or full text don’t focus on the proposed topic were excluded. In total 82 articles were included in this present work. As results, the articles show that the biologic drugs brought new therapeutic options, however, they have an elevated cost, which can be softened with the new coming biosimilar drugs. Keywords: Biopharmaceuticals. Biological medicines. Rheumatoid arthritis.